Active energy ray curable composition and metal molded article
The active energy ray curable composition, comprising urethane (meth)acrylate, a specific polymer, and a monomer, addresses the issue of insufficient sunscreen resistance in existing compositions, achieving superior adhesion, bending properties, and sunscreen resistance for metal substrates.
Patent Information
- Application Number
- JP2018058546
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2018-03-26
- Publication Date
- 2025-04-30
- Estimated Expiration
- 2038-03-26
AI Technical Summary
Existing curable compositions for metal substrates have insufficient resistance to sunscreens, despite providing good adhesion and bending properties.
An active energy ray curable composition comprising urethane (meth)acrylate, a polymer with a hydroxyl value of 50 to 180 mgKOH/g, and a monomer with (meth)acryloyl groups, along with a silane coupling agent, to enhance adhesion, bending properties, and resistance to sunscreens.
The composition achieves excellent adhesion, bending properties, and resistance to sunscreens, making it suitable for forming cured products on metal substrates.
Smart Images

Figure 0007670456000001 
Figure 0007670456000002
Abstract
Description
[Technical field]
[0001] The present invention relates to an active energy ray-curable composition suitable for forming a cured product that has excellent adhesion to metal substrate molded articles, bendability, and resistance to sunscreen agents upon irradiation with active energy rays. [Background technology]
[0002] Metal substrates have advantages such as relatively low cost, toughness, productivity, moldability, and light weight, and thus a hard coat layer is formed on the surface of the metal substrate, and the metal substrate is widely used in the fields of decorative articles, home appliances, etc. Also, molded articles in which an undercoat layer (primer layer) is formed and then subjected to a metallization treatment such as ionization deposition or sputtering are widely used in the fields of decorative articles, home appliances, etc. However, in recent years, the physical properties required for the curable composition forming the hard coat layer or undercoat layer are becoming increasingly high, and a curable composition suitable for forming a cured product having excellent adhesion, foldability, and resistance to sunscreen agents is required.
[0003] Patent Document 1 describes a hard coat paint composition for metal substrates that uses a component having a specific solid content acid value to improve adhesion to metal substrates. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2012-167204 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, the cured product obtained by curing the composition described in Patent Document 1 has a problem in that it has insufficient resistance to sunscreen agents.
[0006] The present invention has been made to solve the above problems, and an object of the present invention is to provide an active energy ray-curable composition suitable for forming a cured product having excellent adhesion, bendability, and resistance to sunscreen agents. Another object of the present invention is to provide a metal molded article having a cured product of the composition. [Means for solving the problem]
[0007] The above problems are solved by the present inventions [1] to [6] below. [1] An active energy ray-curable composition comprising: a urethane (meth)acrylate (A), a polymer (B) having a hydroxyl value of 50 to 180 mgKOH / g, and a monomer (C) having a (meth)acryloyl group. [2] The active energy ray-curable composition according to [1], wherein the (A) is contained in an amount of 5 to 35 mass % based on the total mass of the (A), the polymer (B) and the monomer (C). [3] The active energy ray-curable composition according to [1] or [2], wherein the polymer (B) is contained in an amount of 15 to 45 mass% based on the total mass of the (A), the polymer (B) and the monomer (C). [4] The active energy ray-curable composition according to any one of [1] to [3], wherein the polymer (B) has a mass average molecular weight of 10,000 to 50,000. [5] The active energy ray-curable composition according to any one of [1] to [4], further comprising a silane coupling agent. [6] A metal molded article having a cured product of the active energy ray-curable composition according to any one of [1] to [5] on a metal substrate. Effect of the Invention
[0008] According to the present invention, it is possible to provide an active energy ray-curable composition suitable for forming a cured product having excellent adhesion, bendability, and resistance to sunscreen agents. Also, according to the present invention, it is possible to provide a metal molded article having a cured product of the composition. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] The present invention will be described in detail below. In the present invention, "(meth)acrylate" means one or both of "acrylate" and "methacrylate", "(meth)acrylic" means one or both of "acrylic" and "methacrylic", "(meth)acryloyl" means one or both of "acryloyl" and "methacryloyl", and "(meth)acrylonitrile" means one or both of "acrylonitrile" and "methacrylonitrile".
[0010] The active energy ray-curable composition of the present invention contains a urethane (meth)acrylate (A), a polymer (B) having a hydroxyl value of 50 to 180 mgKOH / g, and a monomer (C) having a (meth)acryloyl group.
[0011] The urethane (meth)acrylate (A) imparts bendability to the cured product of the curable composition of the present invention. In order to improve the bendability of the cured product and the adhesion to a metal substrate, the blending ratio of the urethane (meth)acrylate (A) is preferably 5 to 35 mass %, more preferably 15 to 30 mass %, based on the total mass of the (A), the polymer (B), and the monomer (C).
[0012] In the present invention, the urethane (meth)acrylate (A) is a urethane (meth)acrylate obtained by a urethanization reaction of a polyisocyanate (a1), a polyether polyol (a2), and a compound having a hydroxyl group and a (meth)acryloyloxy group (a3). The polyisocyanate (a1) imparts flexibility to the cured product of the curable composition of the present invention.
[0013] As the polyisocyanate (a1), those used in the production of known urethane (meth)acrylates can be used. Examples of the polyisocyanate (a1) include aromatic polyisocyanates such as 1,3-phenylene diisocyanate, 1,4-phenylene diisocyanate, 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, 2,4-diphenylmethane diisocyanate, and 4,4'-diphenylmethane diisocyanate; ethylene diisocyanate, hexamethylene diisocyanate, 2,2,4-trimethylhexamethylene diisocyanate, and 2,4,4 Aliphatic polyisocyanates such as -trimethylhexamethylene diisocyanate, lysine diisocyanate, and lysine triisocyanate; alicyclic polyisocyanates such as isophorone diisocyanate, dicyclohexylmethane-4,4'-diisocyanate, and methylcyclohexylene diisocyanate; aromatic aliphatic polyisocyanates such as xylylene diisocyanate and tetramethylxylylene diisocyanate; and biuret and allophanate forms of these.
[0014] Among these, aliphatic skeleton diisocyanates such as 1,3-phenylene diisocyanate, 1,4-phenylene diisocyanate, 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, 2,4-diphenylmethane diisocyanate, 4,4'-diphenylmethane diisocyanate isophorone diisocyanate, bis(4-isocyanatocyclohexyl)methane, 1,2-hydrogenated xylylene diisocyanate, 1,4-hydrogenated xylylene diisocyanate, hydrogenated tetramethylxylylene diisocyanate, norbornane diisocyanate, 2,4,4-trimethylhexamethylene diisocyanate, and 2,2,4-trimethylhexamethylene diisocyanate are preferred because they can impart excellent toughness to the cured product of the curable composition of the present invention. The compound (a1) may be used alone or in combination of two or more compounds.
[0015] Moreover, the polyether polyol (a2) imparts flexibility to the cured product of the curable composition of the present invention.
[0016] Examples of the polyether polyol (a2) include polyethylene glycol, polypropylene glycol, polytetramethylene glycol, and 1-methylbutylene glycol.
[0017] Among these, it is particularly preferable to use one or more of polyethylene glycol, polypropylene glycol, and polytetramethylene glycol, in order to impart good flexibility to the resulting cured product. The compound (a2) may be used alone or in combination of two or more compounds.
[0018] The compound (a3) having a hydroxyl group and a (meth)acryloyloxy group may be, for example, one in which the hydroxyl group forms a urethane bond with an isocyanate group of an organic isocyanate compound or an intermediate compound having an isocyanate group obtained from an organic isocyanate compound, thereby introducing a (meth)acryloyloxy group into the urethane (meth)acrylate (A).
[0019] Examples of the compound (a3) include (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, cyclohexanedimethanol mono(meth)acrylate, trimethylolpropane di(meth)acrylate, and pentaerythritol tri(meth)acrylate, as well as caprolactone adducts of these (meth)acrylates. Among these, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate are preferred because they can reduce the viscosity of the urethane (meth)acrylate (A). The compound (a3) may be used alone or in combination of two or more kinds.
[0020] Furthermore, in the present invention, a compound (a4) other than the above (a1) to (a3) may be used during the urethane reaction. Examples of the compound (a4) include polyhydric alcohols such as alkanediols, polycarbonate diols, polycaprolactone diols, and amide diols.
[0021] Examples of the alkanediol include polyhydric alcohols such as neopentyl glycol, ethylene glycol, diethylene glycol, propylene glycol, 1,6-hexanediol, 1,4-butanediol, 1,9-nonanediol, 1,10-decanediol, 3-methylpentanediol, 2,4-diethylpentanediol, tricyclodecane dimethanol, 1,4-cyclohexane dimethanol, 1,2-cyclohexane dimethanol, 1,3-cyclohexane dimethanol, cyclohexanediol, hydrogenated bisphenol A, trimethylolpropane, and pentaerythritol. Examples of polyester diols include polyhydric alcohols such as neopentyl glycol, ethylene glycol, diethylene glycol, propylene glycol, 1,6-hexanediol, 1,4-butanediol, 1,9-nonanediol, 1,10-decanediol, 3-methylpentanediol, 2,4-diethylpentanediol, tricyclodecane dimethanol, 1,4-cyclohexane dimethanol, 1,2-cyclohexane dimethanol, 1,3-cyclohexane dimethanol, cyclohexanediol, hydrogenated bisphenol A, trimethylolpropane, and pentaerythritol; and polyols obtained by reacting these polyhydric alcohols with polybasic acids such as succinic acid, phthalic acid, hexahydrophthalic acid, terephthalic acid, adipic acid, azelaic acid, and tetrahydrophthalic acid, or acid anhydrides of these polybasic acids.
[0022] Examples of polycarbonate diols include polycarbonate diols obtained by transesterification of diols such as 1,6-hexanediol, 3-methylpentanediol, 2,4-diethylpentanediol, trimethylhexanediol, 1,4-butanediol, 1,5-pentanediol, and 1,4-cyclohexanediol with carbonates such as ethylene carbonate, dimethyl carbonate, diethyl carbonate, di-n-propyl carbonate, diisopropyl carbonate, dibutyl carbonate, dicyclohexyl carbonate, and diphenyl carbonate.
[0023] Examples of polycaprolactone diols include polyhydric alcohols such as neopentyl glycol, ethylene glycol, diethylene glycol, propylene glycol, 1,6-hexanediol, 1,4-butanediol, 1,9-nonanediol, 1,10-decanediol, 3-methylpentanediol, 2,4-diethylpentanediol, tricyclodecane dimethanol, 1,4-cyclohexane dimethanol, 1,2-cyclohexane dimethanol, 1,3-cyclohexane dimethanol, cyclohexanediol, hydrogenated bisphenol A, trimethylolpropane, and pentaerythritol; polyether-modified polyols obtained by adding alkylene oxides such as ethylene oxide, propylene oxide, and butylene oxide to these polyhydric alcohols; and polycaprolactone polyols obtained by reacting these polyhydric alcohols with lactones such as ε-caprolactone, γ-butyrolactone, γ-valerolactone, and δ-valerolactone.
[0024] Amide diols include, for example, amide polyols obtained by reacting a cyclic hydroxycarboxylic acid ester with ammonia or a compound containing one primary or secondary amino nitrogen.
[0025] In the present invention, the urethane (meth)acrylate (A) can be produced by a known method for producing a urethane (meth)acrylate. For example, a known catalyst such as dibutyltin dilaurate is used to react an organic isocyanate compound (a1) with a diol to obtain a urethane prepolymer. Then, the isocyanate group remaining at the end of the obtained urethane prepolymer is subjected to an addition reaction with a compound (a3) having a hydroxyl group and a (meth)acryloyloxy group.
[0026] Furthermore, the active energy ray-curable composition of the present invention contains the polymer (B) having a hydroxyl value of 50 to 180 mgKOH / g, and thus the cured product obtained from the curable composition of the present invention has good adhesion to a metal substrate and good resistance to sunscreen agents.
[0027] If the hydroxyl value is less than 50 mgKOH / g, the adhesion to the metal substrate and the resistance to the sunscreen agent are insufficient. If the hydroxyl value is more than 180 mgKOH / g, the resistance to the sunscreen agent is insufficient. From the viewpoint of the adhesion to the metal substrate and the resistance to the sunscreen agent, the hydroxyl value is preferably 100 mgKOH / g or more, and more preferably 160 mgKOH / g or less. From the viewpoint of the resistance to the sunscreen agent, the hydroxyl value is more preferably 150 mgKOH / g or less.
[0028] The hydroxyl value means a value obtained by calculating the amount of free hydroxyl groups contained in 1 g of vinyl (co)polymer from the composition ratio of the monomers used in the polymerization, and then calculating the amount of potassium hydroxide (unit: mg) required to neutralize the acetic acid required to acetylate the hydroxyl groups.
[0029] In the present invention, the polymer (B) is preferably contained in an amount of 15 to 45 mass % and more preferably 30 to 40 mass % based on the total mass of the urethane (meth)acrylate (A), the polymer (B) and the monomer (C). When the blending ratio of the polymer (B) is within the above range, the adhesion to the metal vapor deposition film can be improved.
[0030] Furthermore, in the present invention, the polymer (B) preferably has a mass average molecular weight of 10,000 to 40,000. By adjusting the mass average molecular weight of the polymer (B) to 10,000 to 40,000, the appearance of the cured product of the curable composition can be improved. Furthermore, by adjusting the mass average molecular weight of the polymer (B) to 20,000 to 35,000, the foldability of the cured product of the curable composition can be improved.
[0031] In the present invention, the mass average molecular weight is a mass average molecular weight (Mw) calculated using standard polystyrene standards and measured by gel permeation chromatography (GPC) under the following conditions. Equipment: Tosoh Corporation high-speed GPC equipment HLC-8320GPC type UV detector: Tosoh UV-8320 Flow rate: 0.35mL / min Inlet temperature: 40℃ Oven temperature: 40℃ RI temperature: 40℃ UV wavelength: 254nm Sample injection volume: 10 μL Columns: Three columns connected in the order of (1) to (3). (1) Tosoh TSKgel superHZM-M (4.6mm ID x 15cm L) (2) Tosoh TSKgel superHZM-M (4.6mm ID x 15cm L) (3) Tosoh TSKgel HZ2000 (4.6mm ID x 15cm L) Guard column: Tosoh TSKguardcolumn SuperHZ-L (4.6mm ID x 3.5cm L) Solvent: THF (stabilized with BHT) Sample concentration: Resin content adjusted to 0.2% by mass
[0032] The polymer (B) can be obtained by polymerizing a mixture of monomers including a monomer having a hydroxyl group.
[0033] Examples of monomers having a hydroxyl group include the following hydroxyl group-containing vinyl monomers. Hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate; ethylene oxide adducts of 2-hydroxyethyl (meth)acrylate; propylene oxide adducts of 2-hydroxyethyl (meth)acrylate; ε-caprolactone adducts of 2-hydroxyethyl (meth)acrylate; and organic lactone adducts of 2-hydroxyethyl (meth)acrylate. Among these, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate are preferred from the viewpoint of adhesion between the cured product and the substrate. The monomers having a hydroxyl group can be used alone or in combination of two or more.
[0034] The monomer mixture may contain other monomers in addition to the monomer having a hydroxyl group. The other monomer is a monomer copolymerizable with a monomer having a hydroxyl group, for example, methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, n-butyl (meth)acrylate, t-butyl (meth)acrylate, isobutyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-nonyl (meth)acrylate, cyclohexyl (meth)acrylate, benzyl (meth)acrylate, dicyclopentanyl (meth)acrylate, dicyclopentenyl (meth)acrylate, 2-dicyclopentenoxyethyl (meth)acrylate, isobornyl (meth)acrylate, methoxyethyl (meth)acrylate, ethoxyethyl (meth)acrylate, butoxyethyl (meth)acrylate, methoxyeth ... Examples of the monomer include acrylic esters such as diethyl (meth)acrylate, ethoxyethoxyethyl (meth)acrylate, and tetrahydrofurfuryl (meth)acrylate; styrene or styrene derivatives such as styrene, α-methylstyrene, pt-butylstyrene, and vinyltoluene; acrylamide compounds such as N,N-dimethyl (meth)acrylamide and N,N-diethyl (meth)acrylamide; unsaturated carboxylic acids such as (meth)acrylic acid, itaconic acid, maleic acid, and fumaric acid; polymerizable unsaturated nitriles such as (meth)acrylonitrile; unsaturated carboxylic esters such as diethyl maleate, dibutyl maleate, diethyl itaconate, dibutyl itaconate, diethyl fumarate, and dibutyl fumarate; and vinyl esters such as vinyl acetate and vinyl propionate.
[0035] The polymer (B) can be produced by a known polymerization method such as a solution polymerization method, a bulk polymerization method, or an emulsion polymerization method in the presence of a radical polymerization initiator. In order to adjust the hydroxyl value of the polymer (B) to 50 to 180 mgKOH / g, the amount of the monomer having a hydroxyl group to be used relative to all the monomers used in the production of the polymer (B) may be adjusted.
[0036] Furthermore, the active energy ray-curable composition of the present invention can be cured by active energy rays by containing the monomer (C) having a (meth)acryloyl group.
[0037] Examples of the monomer (C) include monofunctional (meth)acrylates having a polymerizable unsaturated bond such as polyester (meth)acrylates and (meth)acrylates, polyfunctional (meth)acrylates, and epoxy (meth)acrylates, and may be appropriately selected depending on the required performance of the cured product. Examples of monofunctional (meth)acrylates include methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, propyl (meth)acrylate, n-butyl (meth)acrylate, i-butyl (meth)acrylate, t-butyl (meth)acrylate, hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, stearyl (meth)acrylate, morpholyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, glycidyl (meth)acrylate, dimethylaminoethyl (meth)acrylate, and diethyl Examples of the mono(meth)acrylate include mono(meth)acrylates such as aminoethyl (meth)acrylate, tricyclodecane (meth)acrylate, polyethylene glycol mono(meth)acrylate, cyclohexyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, dicyclopentanyl (meth)acrylate, dicyclopentenyl (meth)acrylate, isobornyl (meth)acrylate, allyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, benzyl (meth)acrylate, phenoxyethyl (meth)acrylate, and phenyl (meth)acrylate; and mono(meth)acrylate compounds such as an adduct of phthalic anhydride and 2-hydroxyethyl (meth)acrylate.
[0038] Examples of polyfunctional (meth)acrylates include neopentyl glycol di(meth)acrylate, ethylene glycol di(meth)acrylate, polyethylene glycol (number of repeating units (hereinafter referred to as "n") = 2 to 15) di(meth)acrylate, polypropylene glycol (n = 2 to 15) di(meth)acrylate, polybutylene glycol (n = 2 to 15) di(meth)acrylate, 2,2-bis(4-(meth)acryloxyethoxyphenyl)propane, 2,2-bis(4-(meth)acryloxydiethoxyphenyl)propane, trimethylolpropane diacrylate, bis(2-(meth)acryloxyethyl)-hydroxyethyl-isocyanurate ... Examples of the polyester poly(meth)acrylate include propane tri(meth)acrylate, tris(2-(meth)acryloxyethyl)isocyanurate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, polyester (meth)acrylate obtained by reacting trimethylolethane with succinic acid and (meth)acrylic acid, and polyester (meth)acrylate obtained by reacting trimethylolpropane with succinic acid, ethylene glycol, and (meth)acrylic acid.
[0039] Examples of epoxy (meth)acrylates include those obtained by reacting glycidyl ether compounds such as phenol novolac type epoxy resins, cresol novolac type epoxy resins, bisphenol A type epoxy resins, bisphenol F type epoxy resins, polyglycol diglycidyl ethers, monoglycidyl ethers, fluorene-based epoxy resins, and polyfunctional aliphatic epoxy compounds with (meth)acrylic acid or a derivative thereof.
[0040] Specific examples include a compound in which (meth)acrylic acid is added to a copolymer of epichlorohydrin and bisphenol A, a compound in which (meth)acrylic acid is added to a copolymer of epichlorohydrin and hydrogenated bisphenol A, a compound in which (meth)acrylic acid is added to a copolymer of epichlorohydrin and bisphenol F, a compound in which (meth)acrylic acid is added to a copolymer of epichlorohydrin and brominated bisphenol A, a compound in which (meth)acrylic acid is added to a copolymer of epichlorohydrin and brominated bisphenol A, a compound in which (meth)acrylic acid is added to a glycidyl etherified phenol novolac, a compound in which (meth)acrylic acid is added to a glycidyl etherified o-cresol novolac, and 1,6-hexanediol diglycidyl ether. Examples of such compounds include compounds in which (meth)acrylic acid is added to polyfunctional aliphatic epoxy resins such as 1,4-butanediol diglycidyl ether, cyclohexanedimethanol diglycidyl ether, and neopentyl glycol diglycidyl ether; compounds in which (meth)acrylic acid is added to polyalkylene glycol diglycidyl ethers such as polyethylene glycol diglycidyl ether and polypropylene glycol diglycidyl ether; compounds in which (meth)acrylic acid is added to bisphenol fluorene diglycidyl ether; and compounds in which (meth)acrylic acid is added to bisphenoxyethanol fluorene diglycidyl ether.
[0041] Among these, phenol novolac type epoxy resins, cresol novolac type epoxy resins, and bisphenol A type epoxy resins are preferred because they can impart excellent resistance to sunscreen agents to the cured product of the curable composition. These can be used alone or in combination of two or more.
[0042] In order to improve the adhesion to the metal vapor deposition film and the smoothness of the cured product, the blending ratio of the monomer (C) is preferably 20 to 80 mass %, more preferably 30 to 65 mass %, based on the total mass of the urethane (meth)acrylate (A) and the polymer (B).
[0043] The curable composition of the present invention may further contain a photopolymerization initiator (D). The photopolymerization initiator (D) is a component that cures the curable composition by irradiation with active energy. Examples of the photopolymerization initiator (D) include benzophenone-type initiators such as benzophenone, 4-methylbenzophenone, 2,4,6-trimethylbenzophenone, methyl orthobenzoylbenzoate, and 4-phenylbenzophenone; anthraquinone-type initiators such as t-butylanthraquinone and 2-ethylanthraquinone; 2-hydroxy-2-methyl-1-phenylpropan-1-one, oligo{2-hydroxy-2-methyl-1-[4-(1-methylvinyl)phenyl]propanone}, benzyl dimethyl ketal, 1-hydroxycyclohexyl phenyl ketone, benzoin methyl ether, 2-methyl-[4-(methylthio)phenyl]-2-morpholino-1-propanone, and 2-hydroxy-1-[4-[4 alkylphenone types such as 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butanone-1, diethylthioxanthone, and isopropylthioxanthone; acylphosphine oxide types such as 2,4,6-trimethylbenzoyldiphenylphosphine oxide, bis(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphine oxide, and bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide; and phenylglyoxylate types such as phenylglyoxylic acid methyl ester. These can be used alone or in combination of two or more. Among these, benzophenone and 1-hydroxycyclohexyl phenyl ketone are more preferred from the viewpoint of the curability of the curable composition.
[0044] From the viewpoint of the curability of the curable composition and reducing the amount of the photopolymerization initiator remaining in the obtained cured product, the blending ratio of the photopolymerization initiator (D) is preferably 0.1 to 20 parts by mass, more preferably 0.5 to 15 parts by mass, and even more preferably 1 to 10 parts by mass, based on the total mass of the urethane (meth)acrylate (A), the polymer (B), and the monomer (C).
[0045] Furthermore, if necessary, a known photosensitizer such as methyl 4-dimethylaminobenzoate, ethyl 4-dimethylaminobenzoate, amyl 4-dimethylaminobenzoate, or 4-dimethylaminoacetophenone may be added to the curable composition of the present invention within a range that does not impair the performance.
[0046] In addition, the curable composition of the present invention can be mixed with an organic solvent to adjust the viscosity to a desired level as necessary.The organic solvent includes ketone compounds such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone; ester compounds such as methyl acetate, ethyl acetate, butyl acetate, ethyl lactate, and methoxyethyl acetate; ether compounds such as diethyl ether, ethylene glycol dimethyl ether, diethylene glycol monoethyl ether, diethylene glycol monobutyl ether, and dioxane; aromatic compounds such as toluene and xylene; aliphatic compounds such as pentane, hexane, and petroleum naphtha; alcohol compounds such as isopropyl alcohol, isobutanol, and n-butanol; and propylene glycol compounds such as 1-methoxypropanol and 1-methoxypropanol acetate.
[0047] The curable composition of the present invention further preferably contains a silane coupling agent. Examples of the silane coupling agent include vinyltrimethoxysilane, vinyltriethoxysilane, vinyl-tris(2-methoxyethoxy)silane, N-(2-aminoethyl)3-aminopropylmethyldimethoxysilane, N-(2-aminoethyl)3-aminopropyltrimethoxysilane, 3-ureidopropyltriethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltri ... Examples of the silane include methoxysilane, 3-chloropropylmethyldimethoxysilane, 3-chloropropyltrimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, N-(1,3-dimethylbutylidene)-3-(triethoxysilyl)-1-propanamine, N-[2-(vinylbenzylamino)ethyl]-3-aminopropyltrimethoxysilane hydrochloride, and N,N-bis[3-(trimethoxysilyl)propyl]ethylenediamine. These can be used alone or in combination of two or more. Among these, amino group-containing alkylalkoxysilanes such as N-(2-aminoethyl)3-aminopropylmethyldimethoxysilane and N-(2-aminoethyl)3-aminopropyltrimethoxysilane, and glycidyl group-containing alkylalkoxysilanes such as 3-glycidoxypropyltrimethoxysilane and 3-glycidoxypropylmethyldimethoxysilane are more preferred because of their excellent adhesion to both metal substrates and metal vapor-deposited films. The blending ratio of the silane coupling agent is preferably 0.3 to 5 mass %, and more preferably 0.5 to 3 mass %, based on the total mass of the urethane (meth)acrylate (A), the polymer (B), and the monomer (C), in terms of improving the appearance, adhesion, and abrasion resistance of the cured product of the obtained curable composition to sunscreen.
[0048] The curable composition of the present invention may contain additives such as a leveling agent, an antifoaming agent, an antisettling agent, a lubricant, an abrasive, an antirust agent, an antistatic agent, a light stabilizer, an ultraviolet absorber, a polymerization inhibitor, etc. Furthermore, to the extent that the effects of the present invention are not impaired, a polymer such as an acrylic polymer or an alkyd resin may be added to improve adhesion.
[0049] The curable composition of the present invention can be prepared by mixing the components in a commonly used mixer.
[0050] The curable composition of the present invention can be used as a hard coat layer for the purpose of surface modification of a metal substrate, etc. The composition of the present invention can also be used as an undercoat layer of a cured product in a metal molded product having a cured product and a metal vapor deposition film in that order on a metal substrate.
[0051] Examples of the metal substrate include stainless steel, aluminum, and various steel plates.
[0052] The formation of a hard coat layer or an undercoat layer on the metal substrate is achieved by applying the curable composition of the present invention to the surface of the metal substrate and irradiating it with active energy rays. The curable composition of the present invention can be applied by brush coating, spray coating, dip coating, spin coating, flow coating, or the like. From the viewpoints of coating workability and the smoothness and uniformity of the coating film, the spray coating method and the flow coating method are preferred.
[0053] When the curable composition of the present invention is applied with the organic solvent, it is preferable to volatilize the solvent before curing the curable composition by heating with an IR heater and / or hot air at 30 to 70° C. for 2 to 8 minutes.
[0054] Examples of active energy rays used to cure the curable composition of the present invention include ultraviolet rays, electron beams, etc. For example, when a high-pressure mercury lamp is used, the amount of ultraviolet energy irradiated is 500 to 2000 mJ / cm.2 Conditions of about 100 to 200 nm are preferable. The thickness of the hard coat layer or undercoat layer is preferably in the range of 3 to 40 μm in terms of the thickness of the cured film. EXAMPLES
[0055] The present invention will be described in detail below with reference to examples and comparative examples, but the present invention is not limited thereto. In the following, all "parts" mean "parts by mass" and all "%" mean "% by mass". In addition, various measurements and evaluations in the examples and comparative examples were performed by the following methods.
[0056] 1. Evaluation laminate (1) The obtained curable composition was spray-coated on the surface of a rectangular flat aluminum test piece having a length of 9 cm, a width of 5 cm and a thickness of 2 mm, so that the thickness of the coating film after curing was about 15 μm. The organic solvent was then evaporated by heating in an oven at a temperature of 60° C. for 3 minutes. Thereafter, in the air, a high-pressure mercury lamp was used from above the coated surface to irradiate the coating with an integrated light quantity of 1000 mJ / cm 2 . 2 The coating was cured by irradiating the coating with ultraviolet rays of 340 to 380 nm. The amount of light was measured using an actinometer (trade name UV-351 (SN type) manufactured by Oak Manufacturing Co., Ltd.) to measure the integrated energy amount of ultraviolet rays with wavelengths of 340 to 380 nm. In this manner, an evaluation laminate (1) was produced in which a coating layer was formed on the surface of the substrate. The evaluation laminate (1) was used to evaluate the appearance, adhesion, and performance after a resistance test against a sunscreen agent of the cured product.
[0057] 2. Evaluation laminate (2) A PET film (Cosmoshine A-4300, manufactured by Toyobo Co., Ltd., film thickness 188 μm) was used as a substrate, and the coating was spray-coated on the surface of the substrate so that the coating thickness after curing would be approximately 15 μm. The organic solvent was then evaporated by heating in an oven at 60°C for 3 minutes. Thereafter, in the air, a high-pressure mercury lamp was used to irradiate the coating surface from above with an integrated light quantity of 1000 mJ / cm2. 2The coating was cured by irradiating the coating with ultraviolet light of 1000 nm. The amount of light was measured using an actinometer (trade name UV-351 (SN type) manufactured by Oak Manufacturing Co., Ltd.) to measure the integrated energy amount of ultraviolet light with a wavelength of 340 to 380 nm. In this manner, an evaluation laminate (2) was produced in which a coating layer was formed on the surface of the substrate. The evaluation laminate (2) was used to evaluate the foldability.
[0058] 3. Evaluation method 3-1. Initial appearance The appearance of each laminate for evaluation was evaluated visually to evaluate the appearance of the cured product, and the visual evaluation was judged according to the following criteria. : The surface is smooth and highly glossy. ◯: The surface is smooth, but not very glossy. ×: The surface is uneven and not smooth.
[0059] 3-2. Initial adhesion The cured product formed on the surface of the evaluation laminate was cut with a cutter knife in a grid pattern at 1 mm intervals reaching the base material. 2 A hundred squares were made, cellophane tape was applied on them and then quickly peeled off, and the state of the squares where the interface between the cured product and the aluminum substrate had peeled off was observed. The evaluation was made according to the following criteria: ◎: No peeling in the cross-cut test. Good: No peeling in the cross-cut test, but the cut grooves are slightly chipped. △: Slight peeling in the cross-cut test. ×: Complete peeling in the cross-cut test.
[0060] 3-3. Bendability The laminate for evaluation was folded in the longitudinal direction so that the surface of the cured product formed on the surface of the laminate for evaluation was on the outside, and the presence or absence of cracks in the cured product or peeling of the cured product from the substrate was observed. The evaluation was indicated according to the following criteria. ⊚: Cracks or peeling were observed in the cured material at bending angles of 40° or more. ◯: Cracks or peeling was observed in the cured material at a bending angle of 30°. △: Cracks or peeling was observed in the cured product at a bending angle of 20°. ×: Cracks or peeling was observed in the cured product at bending angles of 10° or less.
[0061] 3-4. Tolerance to sunscreens Sunscreen (Newdrogena Ultra Sheer Dry Touch Sunblock SPF45) 0.2g, 5cm 2 The sunscreen was applied evenly over the entire surface area and left to stand at 50°C for 12 hours, after which the sunscreen was washed off with a large amount of water. After a resistance test to the sunscreen agent, the appearance of the coating film, adhesion to the substrate, and abrasion resistance were evaluated. The results were judged according to the following criteria: ·Appearance of the coating ⊚: No whitening, clouding, bleeding or swelling occurs over the entire coating film. ◯: Either whitening, clouding, bleeding or swelling is observed in part of the coating film. ×: Any of the following phenomena is observed over the entire coating film: whitening, clouding, bleeding, or blisters. - Coating adhesion ◎: No peeling in the cross-cut test. Good: No peeling in the cross-cut test, but the cut grooves are slightly chipped. △: Slight peeling in the cross-cut test. ×: Complete peeling in the cross-cut test. Abrasion resistance The surface of the laminate for evaluation was rubbed back and forth five times with steel wool (Bonstar #0000), and the surface was visually inspected for scratchability to evaluate the abrasion resistance. The evaluation was made according to the following criteria. ◎: No signs of injury. ○: There is a slight scar. △: Scars remain clearly. ×: Many scars remain.
[0062] [Production Example 1] Production of urethane (meth)acrylate (UA-1) A 2 L four-neck flask was charged with 262.35 g (1.00 mol) of bis(4-isocyanatocyclohexyl)methane (manufactured by Sumika Covestro Urethane, product name: Desmodur W) as compound (a1) together with 0.10 g of dibutyltin dilaurate, and the flask was heated in a water bath until the internal temperature reached 60°C. Next, while maintaining the temperature inside the flask at 60°C and stirring the mixture, 217.00 g (0.25 mol) of polyether polyol (manufactured by Hodogaya Chemical Co., Ltd., product name PTG850SN, number average molecular weight 868) as compound (a2) and 33.85 g (0.21 mol) of N-methyl-N-(2-hydroxyethyl)-4-hydroxybutamide (molecular weight 161.2) were uniformly mixed and added dropwise at a constant rate for 4 hours using a dropping funnel equipped with a side tube while maintaining the temperature at 40°C, and further stirred at the same temperature for 2 hours to allow the reaction to proceed. Thereafter, while maintaining the internal temperature of the flask at 70°C, a homogeneous mixed solution of 128.87 g (1.11 mol) of 2-hydroxyethyl acrylate as compound (a3) and 1.23 g of hydroquinone monomethyl ether was added dropwise at a constant rate over 2 hours using a dropping funnel, and further, while maintaining the internal temperature of the flask at 75°C, the mixture was stirred for 4 hours to obtain urethane acrylate UA-1.
[0063] [Production Example 2] Production of copolymer (B-1) The raw materials shown in the column of component 1 in Table 1 were charged into a 2L four-neck flask, and the temperature of the liquid in the flask was heated to 110°C. Next, the liquid in the flask was stirred while maintaining the internal temperature at 110°C, and a monomer-containing mixture consisting of the materials shown in the column of component 2 in Table 1 was dripped into the flask at a constant rate over 4 hours, and then the materials shown in the column of component 3 in Table 1 were added. Then, 1g of azobisisobutyronitrile was added to the flask every hour for a total of four times (total of 4g), and the mixture was stirred for another 2 hours to obtain copolymer (B-1). The mass average molecular weight of this copolymer measured by GPC in terms of polystyrene was 25,000, and the hydroxyl value was 108 mgKOH / g.
[0064] [Production Example 3] Production of copolymer (B-2) A copolymer (B-2) having a mass average molecular weight of 43,000 and a hydroxyl value of 108 mgKOH / g was obtained in the same manner as in Production Example 2, except that 3.8 g of Perbutyl O (registered trademark, manufactured by NOF Corp.) was used as the polymerization initiator used as component 2 and 10 g of Perbutyl O was used as the polymerization initiator used as component 4.
[0065] [Production Example 4] Production of copolymer (B-3) A copolymer (B-3) having a mass average molecular weight of 16,000 and a hydroxyl value of 108 mgKOH / g was obtained in the same manner as in Production Example 2, except that the polymerization initiator used as Component 2 was 10 g of azobisisobutylnitrile.
[0066] [Production Example 5] Production of copolymer (B-4) A copolymer (B-4) having a mass average molecular weight of 22,000 and a hydroxyl value of 150 mgKOH / g was obtained in the same manner as in Production Example 2, except that the monomers used as component 2 were 150 g of styrene (30% of the total monomers) and 175 g of 2-hydroxyethyl methacrylate (35% of the total monomers).
[0067] [Production Example 6] Production of copolymer (B-5) A copolymer (B-5) having a mass average molecular weight of 23,000 and a hydroxyl value of 53 mgKOH / g was obtained in the same manner as in Production Example 2, except that the monomer used as component 2, 2-hydroxyethyl methacrylate (12.5% of all monomers) was replaced with 62.5 g of 2-hydroxyethyl methacrylate (12.5% of all monomers) and 62.5 g of methyl methacrylate (12.5% of all monomers), instead of 125 g (25% of all monomers).
[0068] [Production Example 7] Production of copolymer (B-6) A copolymer (B-6) having a mass average molecular weight of 24,000 and a hydroxyl value of 172 mgKOH / g was obtained in the same manner as in Production Example 2, except that the monomers used as component 2 were 125 g of styrene (25% of the total monomers) and 200 g of 2-hydroxyethyl methacrylate (40% of the total monomers).
[0069] [Production Example 8] Production of copolymer (PB-1) A copolymer (PB-1) having a mass average molecular weight of 20,000 and a hydroxyl value of 0 mgKOH / g was obtained in the same manner as in Production Example 2, except that 125 g of methyl methacrylate (25% of the total monomers) was used instead of 125 g of 2-hydroxyethyl methacrylate (25% of the total monomers).
[0070] [Production Example 9] Production of copolymer (PB-2) A copolymer (PB-2) having a mass average molecular weight of 24,000 and a hydroxyl value of 43 mgKOH / g was obtained in the same manner as in Production Example 2, except that the monomers used as component 2 were 275 g of styrene (20% of the total monomers) and 50 g of 2-hydroxyethyl methacrylate (10% of the total monomers).
[0071] [Production Example 10] Production of copolymer (PB-3) A copolymer (PB-3) having a mass average molecular weight of 25,000 and a hydroxyl value of 194 mgKOH / g was obtained in the same manner as in Production Example 2, except that the monomers used as component 2 were 100 g of styrene (20% of the total monomers) and 225 g of 2-hydroxyethyl methacrylate (45% of the total monomers).
[0072] Example 1 As the urethane (meth)acrylate (A), 15 parts by mass of UA-1 synthesized in Production Example 1, 60 parts by mass (30 parts by mass in terms of solid content) of B-1 polymerized in Production Example 2 as the polymer (B), 35 parts by mass of EA-1: bisphenol A type epoxy acrylate (manufactured by MIWON, product name Miramer PE210), 5 parts by mass of EHA: 2-ethylhexyl acrylate (manufactured by Mitsubishi Chemical, product name 2-ethylhexyl acrylate), and 15 parts by mass of THFA: tetrahydrofurfuryl acrylate (manufactured by Osaka Organic Chemical Industry, product name Viscoat #150) as the monomer (C), 2 parts by mass of HCPK: 1-hydroxycyclohexyl-phenyl ketone and 2 parts by mass of benzophenone as the photopolymerization initiator (D), and 30 parts by mass of toluene, 30 parts by mass of xylene, 30 parts by mass of butyl acetate, and 20 parts by mass of ethyl acetate as organic solvents were mixed and dissolved to obtain a curable composition.
[0073] (Examples 2 to 10, Comparative Examples 1 to 4) A curable composition was prepared, and a laminate for evaluation was produced and evaluated in the same manner as in Example 1, except that the blending and composition were as shown in the composition column in Table 2. The evaluation results are shown in Table 2. The abbreviations used in the examples and comparative examples represent the following compounds.
[0074] UA-1: urethane acrylate obtained in Production Example 1 B-1: Copolymer obtained in Production Example 2 B-2: Copolymer obtained in Production Example 3 B-3: Copolymer obtained in Production Example 4 B-4: Copolymer obtained in Production Example 5 B-5: Copolymer obtained in Production Example 6 B-6: Copolymer obtained in Production Example 7 EA-1: Bisphenol A type epoxy acrylate (MIWON, product name Miramer PE210) EHA: 2-Ethylhexyl acrylate (manufactured by Mitsubishi Chemical, product name: 2-Ethylhexyl acrylate) THFA: Tetrahydrofurfuryl acrylate (Viscoat #150, manufactured by Osaka Organic Chemical Industry Co., Ltd.) HCPK: 1-hydroxycyclohexyl phenyl ketone BNP: Benzophenone PB-1: Copolymer obtained in Production Example 8 PB-2: Copolymer obtained in Production Example 9 PB-3: Copolymer obtained in Production Example 10 KBM-403: 3-glycidoxypropylmethyldimethoxysilane (manufactured by Shin-Etsu Chemical Co., Ltd., product name KBM-403)
[0075] [Table 1]
[0076] [Table 2]
[0077] As shown in Table 2, Comparative Example 1, which did not contain urethane (meth)acrylate (A), had poor folding properties. Comparative Example 2, in which the hydroxyl value of the copolymer was 0 mgKOH / g, had poor initial appearance, initial adhesion, and appearance and adhesion in the resistance test against a sunscreen agent. Comparative Example 3, in which the hydroxyl value of the copolymer was 43 mgKOH / g, had poor adhesion in the resistance test against a sunscreen agent. Comparative Example 4, in which the hydroxyl value of the copolymer was 194 mgKOH / g, had poor initial appearance, and appearance and adhesion in the resistance test against a sunscreen agent.
Claims
1. The epoxy (meth)acrylate comprises a urethane (meth)acrylate (A), a polymer (B) having a hydroxyl value of 50 to 180 mgKOH / g and a mass average molecular weight of 10,000 to 40,000, and a monofunctional (meth)acrylate or epoxy (meth)acrylate as a monomer (C) having a (meth)acryloyl group, the epoxy (meth)acrylate being obtained by reacting at least one selected from the group consisting of a phenol novolac type epoxy resin, a cresol novolac type epoxy resin, a bisphenol A type epoxy resin, and a bisphenol F type epoxy resin with (meth)acrylic acid. wherein the polymer (B) is a polymer obtained by polymerizing a hydroxyl group-containing vinyl monomer and another monomer copolymerizable therewith, and the active energy ray-curable composition is for use as an undercoat layer, which is a cured product, in a metal molded product having, in order, a cured product and a metal vapor-deposited film on a metal substrate (however, the active energy ray-curable composition does not include an unsaturated group-containing acrylic resin having a weight average molecular weight of 5,000 to 70,000, a number of (meth)acrylate functional groups per molecule of 5 to 40, a hydroxyl value of 2 to 200 mgKOH / g, and a glass transition temperature of 20 to 90°C).
2. 2. The active energy ray-curable composition according to claim 1, comprising 5 to 35 mass% of (A) relative to the total mass of (A), the polymer (B), and the monomer (C).
3. The active energy ray-curable composition according to claim 1 or claim 2, comprising 15 to 45 mass% of the polymer (B) relative to the total mass of the (A), the polymer (B), and the monomer (C).
4. The active energy ray-curable composition according to any one of claims 1 to 3, further comprising a silane coupling agent.
5. A metal molded article having a cured product of the active energy ray-curable composition according to any one of claims 1 to 4 on a metal substrate.
Citation Information
Patent Citations
Ultraviolet-curing type coating compound and curing thereof
JP1989011169A
Ultraviolet-curable composition
JP1992209663A
Photocurable type ink composition for printing
JP2008056771A
Hard-coat composition for metal substrate, and molded article
JP2012167204A
Photocurable resin composition and optical film obtained by using the same
JP2014173072A